An exploratory study on the dimensions of spiritual care - Henie Kurniawati; Sofia Retnowati; Bagus Riyono; Widyawati Widyawati (Faculty of Medicine, Universitas Islam Indonesia, 2019)
Background: Spiritual care is one of the important services. The dimensions of spiritual care have not been fully identified clearly. Therefore it is necessary to explore the dimensions of spiritual care.Objective: The aim of this study is to explore spiritual care.Methods: Qualitative research methods were used in order to obtain data through observation techniques, in-depth interviews, and focus group discussions (FGD). The research was conducted within several number of hospitals in Central Java, Indonesia. The samples of this research were 57 nurses with given criteria as following: has a minimum education of associate’s degree in the nursery and a work experience minimum of 2 years in a hospital. Obtained data were, was analyzed with constant comparative and content analysis.Result: The exploration of spiritual care is depicted by hospital nurses as personal belief towards spirituality that can be experienced through spiritual comfort, which is manifested through routine worships, prayers, and intense presence as spiritual implementations and support.Conclusion: This explorative study concludes that there are dimensions in the spiritual care of hospital nurses: personal belief, spiritual knowledge, spiritual comfort, spiritual implementation, and spiritual support. The implications may be able to bring benefit in its application toward the government, hospitals, nurses, patients, and their families, as well as the society.